Cancer-related cognitive impairment in children. Issue 1 (March 2017) - Hutchinson, Amanda D.; Pfeiffer, Susan M.; Wilson, Carlene
Abstract : Purpose of review: To review recent research on cancer-related cognitive impairment (CRCI) in children, including correlational studies and interventions in which outcomes have included cognitive test performance, neuroimaging or academic performance. Recent findings: Impairments in processing speed, working memory, executive function and attention continue to be demonstrated in survivors of childhood cancers. Children receiving radiation treatment for their cancer demonstrate greater impairment than those who undergo surgery and/or chemotherapy without radiation. However, CRCI still occurs in the absence of radiation treatment, particularly in the domain of attention. Recent neuroimaging studies highlight atypical connectivity of white matter and its associations with cognitive performance. Given impairments in cognitive function and associated neuroanatomical factors, it is not surprising that survivors of childhood cancers experience academic difficulties. However, early intervention may provide one means of improving cognitive and academic outcomes. Summary: Children with cancer are at risk of impairment in the domains of processing speed, attention, working memory and executive function. Those who receive radiation are likely to experience greater CRCI than those who do not receive this treatment. All survivors of childhood cancers should be carefully monitored to provide support and implement evidence-based interventions to ameliorate cognitive late effects.